(untitled) (Swiss Medical Weekly, 2020)
A 22-year-old male with a typical history of pauci-symptomatic COVID-19 3 weeks earlier, confirmed by positive serology for SARS-CoV-2 (IgG), was admitted to the intensive care unit because of severe myocarditis with refractory cardiogenic shock that required extracorporeal life support. Due to a clinical presentation suggestive of Kawasaki-like disease with coronary aneurysm and severe systemic inflammation, intravenous immunoglobulins were administered in combination with tocilizumab. The initial clinical course was favourable with these treatments. However, the patient subsequently developed a severe mononeuritis multiplex leading to bilateral foot drop, which required intensive immunosuppressive therapy (corticosteroids, cyclophosphamide and rituximab). The clinical presentation meets the criteria for multisystem inflammatory syndrome associated with SARS-CoV-2, but includes very severe organ damages. Early recognition, a multidisciplinary approach and aggressive therapeutic intervention can lead to a favourable outcome.